Analisis Laporan Keuangan untuk Menilai Kinerja Keuangan Pemerintah Daerah Kabupaten Dairi - sahala Purba; Febri Yoswan Sianturi; Anna Canria Siburian; Missa Kristina Nababan; Yosua Sinaga (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
This research aims to evaluate the financial performance of the Regional Government in Dairi district in the period 2013-2022 by observing 8 financial ratios. The author made observations by collecting information from various document sources in this research. The applied research method uses financial ratio analysis using secondary data from the official publication of the North Sumatra BPK. Time series data that is recorded systematically is then described in detail for evaluating government financial performance and decision making. In this research, it was revealed that the financial performance of the Dairi district government can be explained as follows: (1) the financial independence ratio shows very low results, with an average figure of 7.90%, (2) the regional financial dependence ratio shows low results. high, with an average figure of 90.1%, (3) the ratio of the degree of fiscal decentralization shows very low results, with an average figure of 7.3%, (4) the PAD effectiveness figure shows a very high level of success effective, with an average value of 166.0%, (5) the regional original income (PAD) efficiency ratio has very efficient results, with an average of 0.82%, (6) the regional tax effectiveness figure shows the level of success quite effective, with an average value of 95.8%, (7) the regional tax efficiency ratio has very efficient results, with an average of 4.2%, (8) the BUMD contribution ratio shows quite good results. According to the results of the analysis, it can be said that the implementation and financial management of Dairi district is still inadequate. The suggestion for further research is that qualitative research should be carried out by conducting in-depth interviews regarding the causes and obstacles faced by regional governments in regional financial governance.